ANALISIS PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH DKI JAKARTA PERIODE 2016 – 2021 - Aulia Rahmana Putri (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2022)
The type of this research is associative research. The variables in this study are local revenue, local taxes and regional levies. This study was conducted to test how much influence Regional Taxes and Regional Levies have on the Regional Original Revenue of DKI Jakarta for the period 2016 – 2021. The source of the data used is secondary data, namely the DKI Jakarta PAD Realization Report. This type of approach in this study uses a quantitative approach using the method of multiple linear regression analysis with the help of a test tool in the form of SPSS. Based on the results of the t-test of Regional Tax partially positive and significant effect on the PAD variable. The higher the Regional Tax, the higher the PAD. And vice versa. While the regional levies partially have no significant effect on the PAD variable.